Flow Induced Vibration for Different Support Pipe and Liquids: A review - Adil Mohammed, Ansam; Salman, Ayad Mohammed; Saad Ayoub, Mustafa (Al-Nahrain Journal for Engineering Sciences, 2023)
This study aims to review flow-induced vibration one of the repercussions of vibrations is caused by fluid movement. In general, the investigation of the structure of the systems affects the efficiency of the components that construct those systems. This review examined the influence of generated vibrations and internal pressure on fluid transport pipes using theoretical calculations, practical tests, and numerical analysis to identify and test the dynamic behavior of static fluid transport pipes. The experimental study considered the natural frequencies caused by the fluid pressure effect under various stability situations. The flow of all liquids, such as oil, water, gas, air, and vapors, through the pipes, was tested, and the mathematical models were correctly adjusted. All empirical, theoretical, numerical, and analytical research agrees that several approaches exist to develop, modify, and improve these metrics. However, one factor affecting rheological measurements is vibration, which was addressed as needed in the middle of the 20th century due to major discoveries that damage could be rooted in vibration. Established on the determinations, they provided mathematical models paired with pressure and velocity measurements of moving fluids and the influence of produced or uninduced vibration. This study demonstrates that additional empirical investigations, particularly more detailed analytical methodologies, are urgently required to produce better findings.